Voz e verso : a escrita de Jacinta Passos na década de 1940 no Brasil - Pampani, Alice de Andrade (2024)
The present research has as its object the Jacinta Passos life trajectory and writing in the 1940s. Poet and activist of the Brazilian Communist Party (PCB), Jacinta (1914-1973) used her writing as a political weapon against authoritarian regimes that predominated during the Second World War, including fascism in Europe and integralism in Brazil. This investigation focused on Passos' contributions to the Bahian press, mainly her publications in the magazine Seiva and the newspaper O Imparcial, in which she directed “Página Feminina”, a weekly column in the latter periodical. The methodology that she used involves the construction of concepts such as power, memory and female writing, together with critical discourse analysis, in order to examine how Jacinta's speeches reflect, reproduce or contest ideas and political values of the 1940s. spaces of performance and representation of the poet as a woman, feminist and communist, offers an overview of her ability to move in spaces socially recognized as masculine. Jacinta's collaborations in the press, her poetic works, such as the book “Canção da partida” (Song of Departure) published in 1945, in addition to her own political-partisan speech, are the sources that provided to this research a vision of her life trajectory and the way how the female writing was printed, in part, during the studied period.